UJI KANDUNGAN GIZI DAN PERBANDINGAN SIFAT SENSORIS BERAS ANALOG DARI TEPUNG CASSAVA DENGAN PENAMBAHAN TEPUNG KACANG HIJAU - Nur Annisa Metya Novikasari; Iffah Muflihati; Umar Hafidz Asy'ari Hasbullah; Rizky Muliani Dwi Ujianti (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Analog rice is artificial rice that resembles rice. Cassava flour and mung bean flour are the raw materials used in the manufacture of analog rice. Modification of starch by annealing, Heat Moisture Treatment, and Autoclaving-cooling aims to improve the characteristics of analog rice. This study aims to determine the effect of physical modification of cassava flour and the ratio of flour (modified cassava flour and mung bean flour) on the chemical and sensory properties of analog rice. Making analog rice includes weighing ingredients, mixing, adding water, cooking, extruding, and drying. Chemical analyses were water content, fat content, ash content, protein content and carbohydrate content. A sensory test was conducted using multiple comparison test. The results showed that the type of modification and the ratio of modified cassava flour and mung bean flour were able to reduce water content and fat, but were able to increase ash content , protein and carbohydrates. The comparison test stated that the analog rice was different from the control rice (rice sosoh).